التباين المكاني لبطالة الإناث في العراق لعامي 1997 - 2012 - عبدالرضا، وسن كريم (الجامعة المستنصرية - مركز المستنصرية للدراسات العربية والدولية, 2019)
منذ ثمانينيات القرن الماضي تزايد اعتماد العراق على قطاع النفط، والتوسع غير المستدام لقطاع الخدمات غير المنتجة وبخاصة تلك المتصلة بالمؤسسة العسكرية، مترافقا مع إهمال القطاعات المنتجة كالزراعة والصناعة، وإهمال الاستثمار الإنتاجي في النشاطات المدنية وتزايد سيطرة النخبة الحاكمة على مؤسسات الدولة. وقد تفجرت مشكلة البطالة مباشرة عقب انتهاء الحرب العراقية -الإيرانية مع تسريح ما يقرب من مليون مجند، ليدخلوا سوق العمل دون مهارات تؤهلهم للحصول على عمل ذي دخل مجز. وفي ظل العقوبات الاقتصادية تقيدت قدرة الاقتصاد العراقي على توليد فرص عمل كافية لتشغيل العرض الكبير من القوة العاملة مما أنتج معدل بطالة أخذ يرتفع باستمرار مع فقدان القطاع العام لجاذبيته في التوظيف خلال السنوات (1991-2002) منذ عام ٢٠٠٣ أجريت العديد من مسوحات البطالة التي أشارت إلى انخفاض معدلاتها العامة في البلد من حوالي ٢٨% عام ٢٠٠٣ إلى 17.5% عام 2006 حتى وصلت عام ٢٠١١ الى 11.1% لكن هذه الأرقام تخفي تباينات جغرافية بين المناطق الحضرية والريفية وعلى مستوى النوع وبين المحافظات، تبعا لمدى تأثر تلك المحافظات بالعوامل المؤثرة الاقتصادية منها والاجتماعية والسياسية والأمنية.
Since the 1980, Iraq's dependence on the oil sector has increased, and the unsustainable expansion of the non-productive services sector, especially those related to the military establishment, has been accompanied by the neglect of productive sectors such as agriculture and industry, the neglect of productive investment in civilian activities and the increasing dominance of the ruling elite over state institutions. The problem of unemployment erupted immediately after the end of the Iran-Iraq war with the demobilization of nearly one million recruits to enter the labor market without skills to qualify for a lucrative job. Under economic sanctions, the ability of the Iraqi economy to generate sufficient employment to operate the large supply of labor force has produced an ever-increasing unemployment rate as the public sector lost its attractiveness in employment during the years 1991-2002. Since 2003, many unemployment surveys have been conducted, which indicate a decline in the general rates in the country from about 28% in 2003 to 17.5% in 2006, reaching 11.1% in 2011. However, these figures hide geographical disparities between urban and rural areas and at the level of gender and between governorates, depending on the extent to which those affected by the economic, social, political and security factors.
Keywords: بطالة الإناث -- المرأة العراقية -- المجتمع العراقي -- الاقتصاد العراقي -- العراق